Women and Authorship in the Low Countries: Towards a Differentiated and Collaborative Approach - Dietz, Feike; Geerdink, Nina (Early Modern Low Countries, 2025)
Netherlandish women writing literary texts in the period 1550-1830 are well-studied. The aim of this essay is to show how existing scholarship creates a tension between exceptionalism and marginalisation: scholarship primarily focuses on the challenges female authors faced because of their sex and does so by studying sources surrounding literary publications (such as journals, preliminaries, and portraits), with the notable exception of the works of some canonised women writers who are regarded as exceptions to the rule. As such, early modern Netherlandish women writers are primarily represented as a homogeneous group in scholarship. Yet, we argue, the diversity of literature (co-)authored by women, as well as the heterogeneous identities of these female authors themselves, invites us to destabilise the idea of ‘the female author’ in at least two interrelated ways: by linking their gender to other factors such as age, health, or race in women’s writing; and by approaching female-authored work as ‘collaborative’, i.e., reflecting different voices and hands, enabling scholars to view women in sometimes understudied roles and sources (such as translators and manuscripts, respectively). The future success of these proposed approaches depends on necessary infrastructural steps, as the digital availability and searchability of female-authored texts from the Low Countries is currently lagging behind that which is necessary.